Complete response to ipilimumab and nivolumab therapy in a patient with extensive extrapulmonary high-grade small cell carcinoma of the pancreas and HIV infection. Issue 1 (9th July 2018) - Husnain, Muhammad; Park, Wungki; Ramos, Juan Carlos; Johnson, Thomas E.; Chan, Joseph; Dasari, Arvind; Mudad, Raja; Hosein, Peter J.
Abstract : Background: Immune checkpoint inhibitors (CPIs) have shown promising results in many solid tumors. There are limited data on the safety and efficacy of these drugs in HIV infected patients as they have traditionally been excluded from CPIs clinical trials. Case presentation: We present a case of an HIV-positive patient with extensive extrapulmonary high-grade small cell carcinoma who was treated with dual CPIs (nivolumab and ipilimumab) with a complete response to therapy and with a manageable safety profile. We performed a comprehensive literature review identifying 62 total HIV positive cases treated with CPIs showing this to be a potentially safe option in HIV-positive patients. Conclusion: HIV infection is not an absolute contraindication to CPI therapy. Our case and others provide justification for ongoing trials of CPI therapy in patients with HIV infection, a group that has traditionally been excluded from clinical trials.